(untitled) (Research, Society and Development, 2022)
The present work addresses the changes imposed by health protection measures with the advent of Covid-19, in particular remote work, which anticipated the use of technological resources and the structure of various jobs. The objective of this study is to promote discussions about government actions in the face of the pandemic, in particular teleworking and its impacts on public organizations. Theoretical questions about organizational culture are addressed, seeking its relationship with the public service of the federal executive and remote work. The methodology used was the narrative bibliographic review and the documentary study, seeking to present the regulations in the public service of the federal executive that disciplined remote work amid the Covid-19 pandemic. Questions about the impact of remote work and different readings for this question are also presented. From what has been presented, it is considered that the changes brought about by remote work can, on the one hand, contribute to a greater deepening of a Public Management focused on results and, on the other hand, by new forms of suffering and maladjustments in the world of work. It is also possible to see the potential of Organizational Culture as a way of offering support for a better balance between the responses demanded by society and the commitment and satisfaction of the servers.